Letters and poems to and from her mentor and other members of her circle - Schürmann, Anna Maria von 1607-1678; Rivet, André 1572-1651 (The other voice in early modern Europe: the Toronto series, 2021)
"This volume presents in translation a remarkable run of the correspondence of Anna Maria van Schurman (1607-1678), covering almost four decades of her life, from 1631 to 1669. Largely unpublished, these manuscript letters and poems to and from her mentor, André Rivet (1572-1651), and other members of her circle show how deeply engaged and respected she was in the traditionally male Latin world of the Republic of Letters"--